Poesia moderna e contemporânea e formação do leitor: a produção poética de Heleno Godoy em sala de aula - Assis, Renata Magalhães Vaz (2018)
The present work is based on the problematic 'How can reading modern and contemporary poetry contribute to the formation of the literary reader?' and aims to discuss the formation of literary readers in the school, from reading poetry. The choice of the corpus of analysis for the research arose from the interest of valuing the poetic production of the native of Goias Heleno Godoy, a poet considered one of the fundamental figures for the poetry produced in Goias, especially in the most recent works. Thus, poems were selected from the books A casa (2001) and Lugar comum e outros poemas (2005), among other poems. For the methodology, the qualitative treatment was given, with na action research carried out in a public school, in the outskirts of the city of Inhumas-GO. This methodology was characterized by an intervention in the classroom with the reading of poems from the books already mentioned, by Heleno Godoy, followed by debates, semistructured questionnaire and other pedagogical activities. As an educational product of the research, it was obtained the production of a documentary made with the natural poet of Goias with the pointers of possibilities for the reading of the poetry in the school.